How do sanctions work? The choice between cartel formation and tacit collusion - Maximilian Andres; Lisa Bruttel; Jana Friedrichsen (ZBW - Leibniz Information Centre for Economics, 2021)
This paper analyzes the inner workings of cartels. To understand how sanctioning institutions prevent cartel formation we study their effect on firms' communication in a laboratory experiment. Using machine learning to organize the chat communication into topics, we find that firms are less likely to communicate explicitly about price fixing when sanctioning institutions are present. At the same time, average prices are lower when communication is less explicit. A mediation analysis suggests that sanctions are effective in hindering cartel formation not only because they introduce a risk of being fined but also by reducing the prevalence of explicit price communication
Keywords: C92; D43; L41; 330; cartel; collusion; communication; machine learning; experiment